2020
DOI: 10.1039/d0ra07274e
|View full text |Cite
|
Sign up to set email alerts
|

Blue light-induced low mechanical stability of ruthenium-based coordination bonds: an AFM-based single-molecule force spectroscopy study

Abstract: A HA–RuII complex was conjugated to a hyaluronan polymer through amide bonds. In AFM experiments using the “multi-fishhook” approach, the cantilever tip made contact with the polymeric molecule, resulting in stretching, indicated by sawtooth-like force-extension curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…By changing metal ion or ligands, species dynamics can be tuned. The mechanical strength of many coordination bonds intensities was measured by AFM-based SMFS, which were approximately in the range of the ~10 2 pN scale [ 81 , 82 , 83 ]. By using the ferredoxin which includes a Fe 2 S 4 cluster as model, we have found that the average of mechanical rupture force of Fe-S bond is ~240 pN ( Figure 3 D) [ 39 ].…”
Section: Dynamic Covalent Chemistrymentioning
confidence: 99%
“…By changing metal ion or ligands, species dynamics can be tuned. The mechanical strength of many coordination bonds intensities was measured by AFM-based SMFS, which were approximately in the range of the ~10 2 pN scale [ 81 , 82 , 83 ]. By using the ferredoxin which includes a Fe 2 S 4 cluster as model, we have found that the average of mechanical rupture force of Fe-S bond is ~240 pN ( Figure 3 D) [ 39 ].…”
Section: Dynamic Covalent Chemistrymentioning
confidence: 99%